The Effect of Ultrasonic Treatment on Some Functional Properties of Egg White. - Gélvez-Ordoñez, Victor Manuel; Mendoza-Galvis, Franklin; Orlando Delgado, Javier (Revista Científica de la Facultad de Ciencias Veterinarias)
Â <!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>This work studied the effect of treatment with a high frequency ultrasound bath (40 kHz and a power of 80 W.) on the pH, foaming capacity and stability of the foam of the white of hens eggs (sample 1/120 hours post laying and sample 2/24 hours post laying). Exposure time was at varied intervals of 0, 5, 10 and 15 mins at 20°C. The samples were stored in refrigeration at 4°C for 3 days. The comparative study of the data was carried out using variance analysis(ANOVA) and surface response analysis (RSA); where it was found that the pH did not show any significant changes(P<0.05) due to the effect of the treatment and remained during storage. On the other hand, the results showed that treatment with ultrasound for ten minutes increased the foaming capacity by 15.84 and 13.07% in samples 1 and 2, respectively. However, the stability of the foam in both samples was seen to diminish by 13.89 and 8.50%